Developments in surface contamination and cleaning. - Kohli, Rajiv, 1947-; Mittal, K. L., 1945- (Elsevier, 2019)
Developments in Surface Contamination and Cleaning: Methods for Assessment and Verification of Cleanliness of Surfaces and Characterization of Surface Contaminants, Volume Twelve, the latest release in the Developments in Surface Contamination and Cleaning series, provides best practices on determining surface cleanliness. Chapters include an introduction to the nature and size of particles, a discussion of cleanliness levels, detailed coverage of measurement methods, characterization methods and analytical methods for evaluating surfaces, and an overview of analysis methods for various contaminants. As a whole, the series creates a unique and comprehensive knowledge base for those in research and development in a variety of industries. Manufacturing, quality control and procurement specification professionals in the aerospace, automotive, biomedical, defense, energy, manufacturing, microelectronics, optics and xerography industries will find this book to be very helpful. In addition, researchers in an academic setting will also find these volumes excellent source books.